The Credit Channel in Middle Income Countries - Aaron Tornell; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2003)
With inflation under control in many in middle income countries (MICs), it is now swings in credit, investment and asset prices that affect these countries the most. In this paper we present a framework to analyze both theoretically and empirically how credit market shocks are propagated and amplified in MICs.The strength of the credit channel in our model derives from two key characteristics of MICs: (i)a sharp asymmetry across the tradables (T) sector and the more bank-dependent nontradables (N) sector; and (ii)a significant degree of currency mismatch in the N-sector. This makes movements in the real exchange rate the driving element in the amplification of shocks. The equilibrium imposes unambiguous contemporaneous linkages among key macroeconomic variables and allows us to derive structural VARs. Estimating these VARs using quarterly data for a group of MICs, we find evidence for a strong credit channel, for a balance sheet effect and for asymmetric sectorial responses. Our findings indicate that inflation targeting is not sufficient to guarantee economic stability, as such policy might overlook the development of lending booms and associated sectorial asymmetries.
Keywords: 330